2011
DOI: 10.1016/j.pain.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Can pain be managed through the Internet? A systematic review of randomized controlled trials

Abstract: Given the increasing penetration and health care related use of the Internet, we examined the evidence on the impact of Internet-based interventions on pain. A search of Medline, CINAHL, PsycINFO, and the Cochrane Library was conducted for literature published from 1990 to 2010 describing randomized controlled trials that assessed the effects of Internet-based interventions on patients with pain of any kind. Of 6724 citations, 17 articles were included. The studies evaluated the effects of interventions that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
191
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(209 citation statements)
references
References 43 publications
9
191
2
7
Order By: Relevance
“…Internetdelivered interventions with peer-to-peer support are showing positive effects on health outcomes. 55 The findings of this study provide detailed evidence on design features that users suggest may improve uptake and adherence to online health interventions for insomnia and other mental health complaints. Further research is needed to determine whether incorporation of these attributes is associated with increased use, greater adherence, and consequently improved health outcomes.…”
Section: Strengths and Limitationsmentioning
confidence: 86%
“…Internetdelivered interventions with peer-to-peer support are showing positive effects on health outcomes. 55 The findings of this study provide detailed evidence on design features that users suggest may improve uptake and adherence to online health interventions for insomnia and other mental health complaints. Further research is needed to determine whether incorporation of these attributes is associated with increased use, greater adherence, and consequently improved health outcomes.…”
Section: Strengths and Limitationsmentioning
confidence: 86%
“…28 De resultaten van deze review zijn vergelijkbaar met eerdere reviews en meta-analyses die kleine tot middelgrote effecten vonden bij psychologische klachten, [9][10][11][12][13][14][15][16][17][18] voor patiënten met gezondheidsproblemen [19][20][21][22][23][24]57 en voor face-to-face CGt. 1,58,59 Nieuw in onze review is dat we ook de meer recente studies meenamen, de rol van behandelduur onderzochten en verschillen in effectiviteit voor specifieke categorieën van uitkomstmaten lieten zien.…”
Section: Effectiviteit Van Ecgt Interventiesunclassified
“…[9][10][11][12][13][14][15][16][17][18] Steeds meer studies laten zien dat internetinterventies ook effectief kunnen zijn voor psychologische en lichamelijke klachten bij mensen met gezondheidsproblemen [19][20][21][22][23][24] en in het bevorderen van gezondheidsgedrag, zoals meer bewegen en gezonder eten. 25,26 Om te onderzoeken of eCGt eveneens effectief is bij chronische somatische aandoeningen, moeten de resultaten van het toenemende aantal recente studies systematisch geëvalueerd en kwantitatief geanalyseerd worden.…”
unclassified
“…This review will synthesize the newly emerging evidence that involve broad range of internet based intervention in broader age group with broader range of diseases including migraine, sciatica, osteoarthritis, rheumatic arthritis, burn pain and others as all these types of pain badly impact the social and economic aspects of one's' life. Additionally, this review will expand upon previous review (Bender et al, 2011) by profoundly probing the recent literature for diverse internet-based interventions. We have tried to expand the findings of these two earlier syntheses by including the evidences El-Metwally 171 from more studies, and by including multidimensional effects of internet based intervention on these diverse groups of pain.…”
Section: Introductionmentioning
confidence: 98%
“…Previous review conducted in 2010 reported that internet-based interventions seem promising for people in pain (Bender et al, 2011). As with the growing population, the need for cost-effective methods that can reduce the traveling cost, increase the knowledge and confidence of managing the unrelieved pain and also positive change of individual in terms of both behavioral and clinical outcomes are in high demands (Fox, 2008).…”
Section: Introductionmentioning
confidence: 99%